2013
DOI: 10.1016/j.sysarc.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Resource management for multimedia applications, distributed in open and heterogeneous home networks

Abstract: International audienceThe home network is an open, heterogeneous and distributed environment where ensuring multimedia ap-plications' quality of service is a main concern. Mechanisms to reserve resources (CPU, memory, network) and architectures using them already exist. However, they require to modify the devices or the applications and they do not take into account the heterogeneity of the home network. This paper presents a non-intrusive and adaptable resource management framework. This framework is develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…e distributed spectrum resource sharing service aims to actively encourage users to share idle network resources, which will be rational and efficient in resource allocation and management according to different users' needs; meanwhile, the game theory was studied and found that it is a sensible conflict and cooperation, and the mathematical model is well suited to solve the problem of greed and selfishness among users in the process of spectrum resource sharing collaboration and competition. Game theory is the dominant resource-sharing research approach [15].…”
Section: Proposed Methodologymentioning
confidence: 99%
“…e distributed spectrum resource sharing service aims to actively encourage users to share idle network resources, which will be rational and efficient in resource allocation and management according to different users' needs; meanwhile, the game theory was studied and found that it is a sensible conflict and cooperation, and the mathematical model is well suited to solve the problem of greed and selfishness among users in the process of spectrum resource sharing collaboration and competition. Game theory is the dominant resource-sharing research approach [15].…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Since the QoSiLAN approach is an approach targeting cross access technology scenarios, other approaches working on layer 1 and layer 2 are not discussed. An approach, most similar to the QoSiLAN framework, has been proposed by Louvel et al [24][25][26], who propose a network resource management framework for multimedia applications distributed in heterogeneous home networks. In this solution to QoS for multimedia applications in LANs, also a central management entity, called the Global Resource Manager (GRM), is used as resource coordinator.…”
Section: Approaches For Qos In Local Area Network Beside Thementioning
confidence: 99%
“…In [39], the authors developed a fair resource allocaiton algorithm based on game theory for wirless multimedia communications. A non-intrusive and adaptable resource management framework, for multimedia applications, distributed in open and heterogeneous home networks is proposed in [40] To the best of our knowledge, only a few attempts towards proposing an all-inclusive approach that demonstrates a cost-effective and dynamic VM resource allocation for a media cloud platform, which not only considers atomic as well as composite multimedia services but also heterogeneous net-work conditions along with the overall utilization of physical servers. There-fore, the exploration of such a comprehensive approach is timely and crucial for considering the proliferation of emerging multimedia cloud computing.…”
Section: Related Workmentioning
confidence: 99%